2018
DOI: 10.21037/tau.2017.12.29
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of MRI-targeted biopsies in men with low-risk prostate cancer on active surveillance by stratifying to PI-RADS and PSA-density, with different thresholds for significant disease

Abstract: BackgroundThe fear of undergrading prostate cancer (PCa) in men on active surveillance (AS) have led to strict criteria for monitoring, which have resulted in good long-term cancer-specific survival, proving the safety of this approach. Reducing undergrading, MRI-targeted biopsies are increasingly used in men with low-risk disease despite their undefined role yet. The objective of this study is to investigate the rate of upgrading using MRI-targeted biopsies in men with low-risk disease on AS, stratified on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 41 publications
3
35
2
Order By: Relevance
“…Similarly, Shaw et al reported superiority of targeted biopsies (TB) over standard TRUS-biopsies [12]. Recent studies emphasize the benefit of additional MRI and MRI-guided biopsy for AS [7,13,14]. In a previously published AS-cohort with a two-year follow-up, our group demonstrated a significantly decreased AS disqualification with initial MRI/TRUS-fusion biopsy, compared to initial 12-core-TRUS-biopsy [7].…”
Section: Introductionsupporting
confidence: 54%
“…Similarly, Shaw et al reported superiority of targeted biopsies (TB) over standard TRUS-biopsies [12]. Recent studies emphasize the benefit of additional MRI and MRI-guided biopsy for AS [7,13,14]. In a previously published AS-cohort with a two-year follow-up, our group demonstrated a significantly decreased AS disqualification with initial MRI/TRUS-fusion biopsy, compared to initial 12-core-TRUS-biopsy [7].…”
Section: Introductionsupporting
confidence: 54%
“…Visible abnormalities were reported as likely to be malignant or equivocal for malignancy. It is possible that five‐point MRI risk categorization may have better risk‐stratified patients in a larger cohort . Kaplan–Meier analysis showed well‐calibrated risk of progression based on the three MRI risk levels that we assigned.…”
Section: Discussionmentioning
confidence: 90%
“…On the basis of the studies reviewed, comprising 8,252 men ( 6 - 21 ), PI-RADS category 1–2, 3, 4 and 5 appear to be equally distributed in all suspicious or positive MRIs, represented by approximately one fourth for each category ( Table 1 ). Furthermore, this distribution is comparable for men with first biopsies (total n=1,855), previously negative biopsies (total n=1,355), and men with active surveillance biopsies (total n=1,198).…”
Section: What Is the Prevalence Of Pi-rads 3 Lesions?mentioning
confidence: 99%
“…Some of these studies reported their results according to the Standards of reporting for MRI-targeted biopsy studies (START) of the prostate ( 22 ), and Gleason grading was correlated to the PI-RADS assessment score 1 to 5. Summary results of these studies ( 7 , 8 , 10 , 12 , 21 , 23 ) are shown in Figures 3 and S1 .…”
Section: What Is the Prevalence Of Cspca In Pi-rads 3 Lesions?mentioning
confidence: 99%
See 1 more Smart Citation